Effective Teaching Research in Chinese Educational Contexts: A General and Dimensional Review. Issue 3 (4th May 2022) - Liu, Xinling; Meng, Lingqi; Kong, Minghui
Abstract: Effective teaching is an important research topic worldwide. This review aims to analyze effective teaching literature in China with respect to general characteristics and conceptional dimensions. Two types of effective teaching literature, empirical studies written in Chinese and written in English, are selected for this review. Stronge's effective teaching framework is adopted for examining the conceptual dimensions in the selected studies. The results taken from the two types of literature reveal different research orientations regarding effective teaching. The literature written in Chinese demonstrates a number of quantitative research studies that, overall, are ill-written from the standard criteria of empirical study writing, including serious design flaws, missing important information, and weak data interpretations. In contrast, the literature written in English tends to focus more on a qualitative research orientation with sufficient overall quality for methodological design. Regarding the effective teaching dimensions, the dimension of the Teacher as a Person is interpreted differently, while the dimension of Implementing Instruction is most often commonly adopted in the two types of literature. We suggest that more studies are needed to conceptualize effective teaching frameworks from macro, meso, and micro levels in order to enhance the quality of effective teaching research in China. Additionally, effective teaching studies related to minority students are rare and deserve future investigation.